Sorting motifs target the movement protein of ourmia melon virus to the trans-Golgi network and plasmodesmata - Ozber, Natali; Margaria, Paolo; Anderson, Charles T.; Turina, Massimo; Rosa, Cristina (Frontiers in Virology, 2022)
Plants have a highly sophisticated endomembrane system targeted by plant viruses for cell-to-cell movement. The movement protein (MP) of ourmia melon virus (OuMV) is delivered to plasmodesmata (PD) and forms tubules to facilitate cell-to-cell movement. In our previous work, we identified the sites of OuMV for correct subcellular localization; however, the pathways involved in PD-targeting of OuMV MP are largely unclear, and their identification was the aim of this work. In this study, we demonstrate that OuMV MP localizes to the trans-Golgi network (TGN) but not to the multivesicular body/prevacuolar compartment or Golgi, and carries two putative sorting motifs, a tyrosine (Y) and a dileucine (LL) motif, near its N-terminus. Substitutions in these motifs result in loss of OuMV infectivity in Nicotiana benthamiana and Arabidopsis. Live cell imaging of GFP-labeled sorting motif mutants reveals that both motifs are required for targeting OuMV MP to PD and for efficient systemic infection but show differences in functionality. Moreover, co-immunoprecipitation assays coupled with mass spectrometry identified a series of host factors that could interact with the OuMV MP and link the MP with various pathways, in particular vesicle trafficking and membrane lipids. Our findings delineate the trafficking route of OuMV MP for PD-targeting and elucidate host factors potentially recruited by OuMV MP that could be modified to impair OuMV infection.